Correlation between salivary and serum anti‐desmoglein 1 and 3 antibody titres using ELISA and between anti‐desmoglein levels and disease severity in pemphigus vulgaris. (22nd May 2017) - De, D.; Khullar, G.; Handa, S.; Joshi, N.; Saikia, B.; Minz, R. W.
Summary: ELISA for anti‐desmoglein antibodies (Dsg) is commonly used for diagnosis and assessment of treatment response in pemphigus vulgaris (PV). The present study was conducted to assess the relationship between salivary and serum Dsg1 and Dsg3 levels, and whether salivary Dsg1 and Dsg3 levels correlate with clinical disease severity of oral mucosal lesions in PV. In total 43, patients with PV with predominantly mucosal involvement were recruited. Both serum and salivary samples were collected from the cases, and salivary samples were also collected from five controls. There was a statistically significant correlation between serum and salivary Dsg1 levels and between serum and salivary Dsg3 levels. There was no correlation between serum or salivary Dsg1 and Dsg3 levels with the objective component of the oral mucosal Autoimmune Bullous Skin Disorder Intensity Score (ABSIS). Serum Dsg1 levels significantly correlated with cutaneous ABSIS, but there was no correlation between cutaneous ABSIS and either salivary Dsg1, salivary Dsg3 or serum Dsg3. As salivary Dsg titres correlate with serum levels, saliva can serve as a simple and noninvasive alternative to serum for Dsg ELISA.